Protective role of DNJ-27/ERdj5 in Caenorhabditis elegans models of human neurodegenerative diseases - Muñoz-Lobato, Fernando; Rodríguez-Palero, María Jesús; Naranjo-Galindo, Francisco Jose; Shepard, Freya; Gaffney, Christopher J.; Szewczyk, Nathaniel J.; Hamamichi, Shusei; Caldwell, Kim A.; Caldwell, Guy A.; Link, Chris D.; Miranda-Vizuete, Antonio (Mary Ann Liebert, 2014)
Aims: Cells have developed quality control systems for protection against proteotoxicity. Misfolded and aggregation-prone proteins, which are behind the initiation and progression of many neurodegenerative diseases (ND), are known to challenge the proteostasis network of the cells. We aimed to explore the role of DNJ-27/ERdj5, an endoplasmic reticulum (ER)-resident thioredoxin protein required as a disulfide reductase for the degradation of misfolded proteins, in well-established Caenorhabditis elegans models of Alzheimer, Parkinson and Huntington diseases. Results: We demonstrate that DNJ-27 is an ER luminal protein and that its expression is induced upon ER stress via IRE-1/XBP-1. When dnj-27 expression is downregulated by RNA interference we find an increase in the aggregation and associated pathological phenotypes (paralysis and motility impairment) caused by human β-amyloid peptide (Aβ), α-synuclein (α-syn) and polyglutamine (polyQ) proteins. In turn, DNJ-27 overexpression ameliorates these deleterious phenotypes. Surprisingly, despite being an ER-resident protein, we show that dnj-27 downregulation alters cytoplasmic protein homeostasis and causes mitochondrial fragmentation. We further demonstrate that DNJ-27 overexpression substantially protects against the mitochondrial fragmentation caused by human Aβ and α-syn peptides in these worm models. Innovation: We identify C. elegans dnj-27 as a novel protective gene for the toxicity associated with the expression of human Aβ, α-syn and polyQ proteins, implying a protective role of ERdj5 in Alzheimer, Parkinson and Huntington diseases. Conclusion: Our data support a scenario where the levels of DNJ-27/ERdj5 in the ER impact cytoplasmic protein homeostasis and the integrity of the mitochondrial network which might underlie its protective effects in models of proteotoxicity associated to human ND.